2015
DOI: 10.1002/sdtp.10391
|View full text |Cite
|
Sign up to set email alerts
|

29.2: Silicon Ink‐Based Poly Si CMOS TFT Fabricated on 300mm Stainless Steel Foil Substrates

Abstract: Laser crystallized CMOS TFTs were fabricated on thin 300 mm stainless steel substrates using novel coated silicon in a Printed Dopant PolySilicon (PDPS) process-flow [1]. Silicon ink will be a key building block for low-cost, continuous large-area coating or printing in very highvolume roll-to-roll manufacturing.RF devices with PECVD-equivalent TFT characteristics using semiconductor-grade inks are routinely fabricated using this process. This technology is foundational to RF (13.56MHz), display and integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…First, a stainless-steel foil substrate compatible with high temperature processing was adopted over silicon wafers. Second, slot die coating of silicon ink was adopted to form the active layer [2] and third, screen printing was adopted for doping. Conventional metal sputtering and lithography were continued from there instead of inkjet for final highresolution processes.…”
Section: Introductionmentioning
confidence: 99%
“…First, a stainless-steel foil substrate compatible with high temperature processing was adopted over silicon wafers. Second, slot die coating of silicon ink was adopted to form the active layer [2] and third, screen printing was adopted for doping. Conventional metal sputtering and lithography were continued from there instead of inkjet for final highresolution processes.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that high performance polysilicon CMOS TFT devices on flexible stainless-steel substrates can be used to make low cost Near-Field Communication (NFC) tags at pilot scale production [4]. This results in a high throughput, low maintenance, and low step count process, capable of migrating to a R2R manufacturing line.…”
Section: Introductionmentioning
confidence: 99%